2023
DOI: 10.1051/e3sconf/202342505001
|View full text |Cite
|
Sign up to set email alerts
|

Building Resilience: Addressing Climate Change Impacts on Rice Production Based on Agricultural Infrastructure in West Java Province, Indonesia

Ali Jamil,
R Ayu Chairunnisya

Abstract: Climate change threatens the sustainability of the agricultural sector and has the potential to affect food availability in West Java, Indonesia’s rice production centre. This study aims to examine how agricultural infrastructure has developed over the past five years and how this has affected the vulnerability index. Climate, production, agricultural infrastructure and facilities data were collected from various sources, including the Central Statistics Agency, the Ministry of Agriculture, and the Directorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Rice cultivation heavily depends on weather conditions, with rainfall being a particularly detrimental factor that can negatively affect production. In West Java, excessive rainfall often leads to severe flooding, which can ultimately result in crop damage and failure [6]. Based on a review of the existing literature, several studies have been conducted, including those that focus on the following areas.…”
Section: The Impact Of Climate Change On the Agromaritime Sectormentioning
confidence: 99%
See 2 more Smart Citations
“…Rice cultivation heavily depends on weather conditions, with rainfall being a particularly detrimental factor that can negatively affect production. In West Java, excessive rainfall often leads to severe flooding, which can ultimately result in crop damage and failure [6]. Based on a review of the existing literature, several studies have been conducted, including those that focus on the following areas.…”
Section: The Impact Of Climate Change On the Agromaritime Sectormentioning
confidence: 99%
“…It is a complex undertaking for the government to improve the village infrastructure and develop agromaritime ecosystems. A study of rice farmers in West Java indicated that the rehabilitation of agricultural machinery, ponds, and tertiary irrigation systems (RTIN) can enhance production on agriculture [6]. The availability of an adequate transportation infrastructure is another crucial socioeconomic factor that presents a significant challenge.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation